The impact of sectoral foreign aid on growth - Saidon, Ruhaida; Yusop, Zulkornain; Ismail, Normaz Wana; Law, Siong Hook (School of Social Sciences, Universiti Sains Malaysia, 2012)
Since donors started providing foreign assistance to developing countries, a broad empirical literature has emerged to investigate the effectiveness of foreign aid on growth of the recipient countries. This substantial and growing body of research in theoretical and empirical literature has increased the knowledge about the effectiveness of foreign aid in promoting growth. This study contributed to the empirics of growing debate on foreign aid-growth nexus by investigating the impact of foreign aid on growth in recipient countries based on disaggregated foreign aid figures. We disaggregated foreign aid into four main sector, which are; (i) aid to social infrastructure and services sector, (ii) aid to economic infrastructure and services sector, (iii) aid to production sector and (iv) aid to multi sector. Then we estimate these sectoral aid disaggregation on growth by utilized the System Generalized Method of Moments (GMM) method. We use a panel data of 83 aid’s recipient countries covering the period of 1995-2009. The results indicated that different sectoral foreign aid exerted different impact on growth. Aid to multi sectors has significant impact in increasing the growth, while aid to economic infrastructure and services sectors was found to decrease growth. In addition, aid to social infrastructure and services and aid to production sectors were positively insignificant and negatively insignificant affected the growth respectively.